If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -2 = 34 + -1t Reorder the terms: -2 + 5t = 34 + -1t Solving -2 + 5t = 34 + -1t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add 't' to each side of the equation. -2 + 5t + t = 34 + -1t + t Combine like terms: 5t + t = 6t -2 + 6t = 34 + -1t + t Combine like terms: -1t + t = 0 -2 + 6t = 34 + 0 -2 + 6t = 34 Add '2' to each side of the equation. -2 + 2 + 6t = 34 + 2 Combine like terms: -2 + 2 = 0 0 + 6t = 34 + 2 6t = 34 + 2 Combine like terms: 34 + 2 = 36 6t = 36 Divide each side by '6'. t = 6 Simplifying t = 6
| 125+10x=230+2x | | (2q-3)q=27 | | 12y+6=12y+7 | | 5x+28=x | | 42+3x(6+1)+4=24 | | 9x+30=27 | | 20-4(p+1.25)=5+p | | 0=-16x^2+16x+320 | | (2w+7)w=99 | | 0.3a+.7=.5a-.1 | | -8(3p+2)+2(-5+7p)=-66 | | 2(x-1)+3x=3(-2+x) | | 1.5*1= | | (2x^2+8x+1)= | | f(x)=15x+10 | | (2w+11)w=63 | | (8-z)(5z-9)=0 | | 5(1-8k)+4(3k+7)=61 | | 2w+11=63 | | -3-2x+5=5+x-2x | | 8+8(-2g+4)=4(-4g+10) | | 7-5(-7b-1)=-8(3-4b) | | 5+x(53)+8=52 | | -3x^2-6x-21=0 | | 13x+3=23+3x | | 7m(m-1)=3(1-m) | | g(b+8)=8x+5 | | (2w-5)w=33 | | X-3-3x=-3(1+x) | | (3x^2+22x-16)= | | -4(x+7)=4(-x+8) | | 12x^2+5x-98=0 |